2003
DOI: 10.1097/01.brs.0000048672.34459.31
|View full text |Cite
|
Sign up to set email alerts
|

The Potential and Limitations of a Cell-Seeded Collagen/Hyaluronan Scaffold to Engineer an Intervertebral Disc-Like Matrix

Abstract: This work demonstrates that although it is possible to maintain functional disc cells in a biomatrix, it will be necessary to optimize proteoglycan synthesis and retention if any resulting tissue is to be of value in the biologic repair of the degenerate disc. The ability of the anulus cells to replicate the matrix production of the nucleus cells, at least in the collagen/hyaluronan scaffold, suggests that repair may not be limited to the availability of authentic nucleus cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
0
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 43 publications
5
128
0
2
Order By: Relevance
“…Exciting advances in the field of tissue engineering have allowed spine researchers to begin developing novel therapeutic approaches in an attempt to intervene in and modulate the course of IVD degeneration by repairing, replacing or regenerating the herniated or degenerated NP [7][8][9][10]. However, these strategies are ineffective without a functional annulus fibrosus (AF) able to withstand the physiological intradiscal pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exciting advances in the field of tissue engineering have allowed spine researchers to begin developing novel therapeutic approaches in an attempt to intervene in and modulate the course of IVD degeneration by repairing, replacing or regenerating the herniated or degenerated NP [7][8][9][10]. However, these strategies are ineffective without a functional annulus fibrosus (AF) able to withstand the physiological intradiscal pressure.…”
Section: Introductionmentioning
confidence: 99%
“…AF tissue engineering approaches have evaluated AF cells seeded in several types of 3D hydrogels or scaffolds [7,[14][15][16][17][18]. These studies have demonstrated that AF cells proliferate in 3D culture and synthesize ECM, reconstituting the histological structure of native tissue.…”
Section: Introductionmentioning
confidence: 99%
“…To induce MSC chondrogenesis growth factors such as transforming growth factor (TGF)-b1, 2 or 3 [18], bone morphogenetic protein-2 [19], -4 [20], -7 [21] or -14 (GDF-5) [22], have been described to facilitate MSCs differentiation, however the aim of this project was to focus on the differences caused by variety of matrixes. In particular, many studies already described culture of MSCs embedded in several types of scaffolds, such as agarose gels [23], alginate beads [24][25][26], synthetic polymers [27,28] and other biomaterials [29][30][31][32]. These studies provide clear evidence that there is a need of a cell support for enhancing cell-cell and cell-matrix interactions and creating a 3D environment.…”
Section: Introductionmentioning
confidence: 99%
“…He could show that cells were viable and that they were able to proliferate after implantation. Alini et al [1], used Collagen-I/Hyaluronan scaffolds to culture nucleus/annulus cells. He showed that the cells proliferate but more proteoglycan was released into the culture medium and did not stay in the implant.…”
Section: Introductionmentioning
confidence: 99%